Podcast Pengetahuan dan Perlindungan Hak Kekayaan Intelektual di Kalangan Akademisi dan Kreator Muda - Lesfandra; Lukas Sugiyanto; Edvin Fairliantina; Dony Oktariswan; Hugo Aries Suprapto; Yocki Pramudya Ananda; Rita Mardiana; Aditya Zakaria Hidayat; Pratiwi Srietiningsih (Academica : Jurnal Pengabdian Kepada Masyarakat, 2025)
The problem of knowledge and protection of Intellectual Property Rights (IPR) among academics and young creators is lacking to protect the results of intellectual creativity. The purpose of community service activities is to create a healthy, competitive, and sustainable creative ecosystem among academics and young creators. This podcast activity uses a qualitative method with stages (1) Material Planning, (2) Selection of Resource Persons, (3) Recording and Production, (4) Publication and Distribution, and (5) Interaction and Evaluation. There were 8 resource persons attended by 43 students. The results of the activity showed an increase in students' understanding of the importance of protecting works and innovations legally, encouraging active student participation, and forming a community that cares about intellectual property protection. Evaluation of the assessment of the understanding of the IPR knowledge podcast with an average score of 96.6%. Students have a very good and comprehensive understanding of various aspects of Intellectual Property Rights presented in the educational podcast.